Cetaceans and cetacean research in India - Kumarran, R. P. (J. Cetacean Res. Manage., 2023)
The diversity of cetacean species in Indian waters is high, with 25 species recorded so far. Records of cetaceans from India during the last 200 years have provided insights into their spatiotemporal distribution, behaviour, feeding, reproduction, fishery interaction and pollution. The cetacean fauna is dominated by pantropical species, with a relatively high abundance of spinner dolphins, which is similar to other areas studied within the northern Indian Ocean. Historical records were analysed to propose an inventory of cetaceans. Cetacean diversity was highest in the Gulf of Mannar on the southeast coast of India, which with 14 species recorded from a small area can be considered a ‘hot spot’ for further research. Fishery interactions, domestic consumption, pollution and lack of quality information to inform management are the main threats for successful survival of cetaceans. The status of information regarding cetaceans in India could be classified based on this study as: six species with adequate data; five species where data is restricted to a few geographic locations; four species for which data collection is being initiated; five species with sparse data; and six species which are difficult to observe.